A Comparison of the Sexual Well-Being of New Parents with Community Couples. Issue 11 (14th September 2020) - Schwenck, Gracielle C.; Dawson, Samantha J.; Muise, Amy; Rosen, Natalie O.
Abstract: Background: Changes in sexual well-being are common for new mothers and their partners after the birth of a baby. However, most research has sampled mothers not couples, assessed only one aspect of sexual well-being, and has not included a control sample of couples. Aim: This study aimed to compare the sexual well-being (ie, sexual frequency, sexual satisfaction, sexual desire, sexual distress) of first-time mothers and their partners in the transition to parenthood (first 12-month postpartum) to community couples who are not actively in this transition. We also compared the sexual well-being within couples (eg, mothers to their partners). Methods: Couples in the transition to parenthood (n = 99) completed measures of sexual satisfaction, sexual desire, sexual distress, and sexual frequency at 3, 6, and 12 months postpartum, and community couples (n = 104) completed the measures at a single time point. Outcomes: Measures included the following: (i) Global Measure of Sexual Satisfaction Scale; (ii) Female Sexual Function Index and International Index of Erectile Function sexual desire subscale; (iii) Female Sexual Distress Scale-Revised; and (iv) checklist of sexual behaviors. Results: Compared with community controls, new parents reported lower sexual satisfaction, lower sexual desire, and higher sexual distress at all time-points; however, these group differences became less pronounced by 12 months postpartum. By 6 months postpartum, there was no difference in sexual frequency between postpartum couples and the control group. Mothers experienced persistently lower sexual desire relative to their partners throughout the 12 months postpartum. Between 39% and 59% of mothers reported clinically low sexual desire, and 47–57% reported significant sexual distress at all time points. There were no significant differences reported in sexual satisfaction, sexual desire, or sexual distress between women and their partners in the community sample. Clinical Implications: Clinicians should be aware that sexual well-being may be compromised in new parents, and some of these challenges are still present for new parents at 12 months postpartum. Findings can be used to educate new parents regarding their expectations about postpartum sexual well-being. Strengths & Limitations: The strengths of the present study are the dyadic approach, assessing multiple aspects of sexual well-being in new parents over time, and the comparison with a community sample. An important limitation is that the control sample was not followed up over time. Conclusion: Education regarding postpartum sexual well-being should be incorporated in routine perinatal and postnatal healthcare practices to support new parents in developing realistic expectations about changes during the transition to parenthood, potentially preventing undue distress.